2021
DOI: 10.3389/fimmu.2021.789735
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells as Predictors of Clinical Course in Hospitalised COVID-19 Patients

Abstract: BackgroundThe host immune response has a prominent role in the progression and outcome of SARS-CoV-2 infection. Lymphopenia has been described as an important feature of SARS-CoV-2 infection and has been associated with severe disease manifestation. Lymphocyte dysregulation and hyper-inflammation have been shown to be associated with a more severe clinical course; however, a T cell subpopulation whose dysfunction correlate with disease progression has yet to be identify.MethodsWe performed an immuno-phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 37 publications
(41 reference statements)
2
23
0
Order By: Relevance
“…Earlier studies investigating patients during acute illness revealed that COVID-19 can induce alterations in lymphocyte frequency and functioning that are associated with disease severity and prognosis (2,40,(67)(68)(69). In severe cases, a loss of CD4 + lymphocytes, including Tregs is a prominent clinical feature that, together with an enhanced myelopoiesis, contributes to an expansion of neutrophils, dendritic cells and macrophages, favoring immunopathology, excessive tissue infiltration and acute respiratory distress syndrome (40,41,(70)(71)(72)(73). Of note, the decrease of Tregs in severe COVID-19 patients is not only a reflection of diminished absolute cell counts in the context of lymphopenia but is also linked to altered relative cell frequencies, as a result of Th17 cell expansion (74).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies investigating patients during acute illness revealed that COVID-19 can induce alterations in lymphocyte frequency and functioning that are associated with disease severity and prognosis (2,40,(67)(68)(69). In severe cases, a loss of CD4 + lymphocytes, including Tregs is a prominent clinical feature that, together with an enhanced myelopoiesis, contributes to an expansion of neutrophils, dendritic cells and macrophages, favoring immunopathology, excessive tissue infiltration and acute respiratory distress syndrome (40,41,(70)(71)(72)(73). Of note, the decrease of Tregs in severe COVID-19 patients is not only a reflection of diminished absolute cell counts in the context of lymphopenia but is also linked to altered relative cell frequencies, as a result of Th17 cell expansion (74).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a trend toward functional impairments and decreased levels of circulating Tregs in severe cases of COVID-19 has been reported previously (3335). It was shown that patients dying from COVID-19 exhibited significantly lower Treg counts and higher Th17/Treg ratio compared to recovered and healthy controls (3739) and that low Treg counts at hospital admission were associated with clinical worsening and longer duration to discharge (40, 41). Correspondingly, several studies demonstrated a downregulation of FoxP3 in severe cases of COVID-19 (39, 42–44).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a single-cell transcriptomic analysis of viral antigen-reactive CD4 + T cells from 40 COVID-19 patients got the conclusion that SARS-CoV-2-reactive Tregs were dramatically reduced in hospitalized COVID-19 patients, while the proportions of cytotoxic follicular helper cells and cytotoxic T helper cells responding to SARS-CoV-2 were increased (80). Other study highlighted that, compared to mild or moderate subjects, the absolute number of total lymphocytes of severe COVID-19 patients was reduced and the amount of Tregs was negatively correlated to viral load, suggesting reduced Tregs stood for increased risk of worsening during the hospitalization (81). A study in Wuhan showed severe COVID-19 patients presented decreased regulatory T cells (CD3 + CD4 + CD25 + CD127 low ) proportion (82).…”
Section: The Change Of Treg In Sars-cov-2 Patients: a Controversial T...mentioning
confidence: 98%
“…The interleukin twelve (IL-12)-induced Th1 subset generates interferon gamma (IFN-g) and tumor necrosis factor (TNF-a) whereas the IL-6 driven Th17 cells generate IL-17 and IL-21 (165). Recent studies have shown significant reduction of T regs in COVID-19 patients, with an imbalance in the Treg/Th17 ratio weakening inflammatory inhibition worsening patient prognosis (166).…”
Section: Purinergic Targets For Sars-cov-2 Induced Pathologiesmentioning
confidence: 99%